Remoção de corantes azos aniônicos por adsorção em sílica gel funcionalizada com 3-Aminopropiltrietoxisilano - Lessa, Raquel Studart de Farias (2018)
This study investigates the potential use of a silica gel modified with the silanizing 3- aminopropyltriethoxysilane as an adsorbent for the removal and possible recovery of the dyes: amaranth, ponceau 4r, acid red 17 and hydroxynaphtol blue, from aqueous solutions synthetic and aqueous industrial effluents. These dyes are anionic chromophore molecular structure. Initially, methods were validated and developed molecular absorption spectrophotometric in the region of the visible, reliable and low cost, for quantification of the azo dyes in aqueous medium, from adsorptive assays. Earplugs and cation sequestrants were used as stabilizing solutions in the methods. They went validated for concentrations of analytes (dyes) in the range of 5 to 60 mg.L-1. A silica gel was modified with the silanizing agent following the procedure of literature. Mean infrared spectra were determined to confirm the modification of the silica gel. The effect of pH, time and the temperature for the adsorbent prepared with each of the four dyes. The adsorptive removal of the dyes (kinetics and equilibrium) were performed in aqueous and batch phase monocomponents. The adsorption kinetic curves obtained were adjusted to pseudopress and pseudase 2 orders. The isotherms of determined were also adjusted using the Langmuir Freundlich. The differences in adsorption behavior of the four dyes with silica gel functionalized were also evaluated, being verified the influence of the auxochromic groups, which differentiate these dyes, in the adsorptive process. In addition, desorption of the dyes was studied with solutions of NaOH, KOH, Na2CO3 in the concentration of 0.025 mol.L-1 and NaHCO 3 of 0.1 mol L-1. In order to verify the efficiency of the adsorbent in real cases, Two samples of industrial effluents were collected: one from the textile industry and another from the foods, which use azide dyes in their production processes. The methods developed and validated were efficient in the quantification of dyes. The acidic pH was the most favorable for the adsorption of the dyes evaluated on the aminofunctionalized silica. An higher adsorption capacity was obtained at 25 ° C. The best models obtained were the pseudomain order and Langmuir models for kinetics and equilibrium, respectively. The time to reach equilibrium was around 6 hours for all dyes. According the Langmuir model, the maximum adsorption capacity of the dyes in the evaluated adsorbent obeys the following order: AR17 <P4R <AR27 <AHN, which shows that the adsorption process is a promising alternative for the removal of azo dyes in aqueous media. The dye that The most adsorbed was hydroxynaphtol blue most likely to have a auxochrome more than the other dyes. The solutions of NaOH and KOH were the best desorption agents to remove the adsorbed dyes at a temperature of 60øC. Silica was able to efficiently remove color from actual industrial effluents, obtaining average removals of 81% and 54% for wastewater from the textile and respectively.